2009
DOI: 10.1021/jp903661r
|View full text |Cite
|
Sign up to set email alerts
|

Low Density Lipoprotein Detection Based on Antibody Immobilized Self-Assembled Monolayer: Investigations of Kinetic and Thermodynamic Properties

Abstract: Human plasma low density lipoprotein (LDL) immunosensor based on surface plasmon resonance (SPR) and quartz crystal microbalance (QCM) was fabricated by immobilizing antiapolipoprotein B (AAB) onto self-assembled monolayer (SAM) of 4-aminothiophenol (ATP). The AAB/ATP/Au immunosensor can detect LDL up to 0.252 microM (84 mg/dL) and 0.360 microM (120 mg/dL) with QCM and SPR, respectively. The SPR and QCM measurements were further utilized to study the reaction kinetics of the AAB-LDL interaction. The adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 46 publications
1
27
1
Order By: Relevance
“…4. Similar values have been found by Matharu et al [29] based on surface plasmon resonance and quartz crystal microbalance fabricated by immobilizing antiapolipoprotein B into a self-assembled monolayer of 4-aminothiophenol. These interesting results showed that the adsorption of oxLDL was slightly different than that of nLDL on the lipid monolayer as discussed below.…”
Section: Lipid Solution and Monolayer Preparation 23 Lipoprotein Solsupporting
confidence: 87%
“…4. Similar values have been found by Matharu et al [29] based on surface plasmon resonance and quartz crystal microbalance fabricated by immobilizing antiapolipoprotein B into a self-assembled monolayer of 4-aminothiophenol. These interesting results showed that the adsorption of oxLDL was slightly different than that of nLDL on the lipid monolayer as discussed below.…”
Section: Lipid Solution and Monolayer Preparation 23 Lipoprotein Solsupporting
confidence: 87%
“…In addition, the use of biosensors offer several benefits over conventional diagnostic tools as simplicity, specificity, speed, low-cost, portable instrumentation and capability for continuous monitoring in real-time (Freire et al, 2002;Malhotra et al, 2006;Zhao & Ju, 2006). LDL sensors (lipoprotein sensors) are a new promising group or bioreceptors, because of their outstanding selectivity and stability in responses that provides an evaluation about biomedical diagnosis in plasma LDL levels (Matharu et al, 2009a(Matharu et al, , 2009b(Matharu et al, , 2010. New methods for diagnosis of LDL employing biosensors are the current demand to evaluate the risk factors for atherosclerosis.…”
Section: Biosensorsmentioning
confidence: 99%
“…The general working principle of the immunosensors is based on the fact that the specific immunochemical recognition of antibodies (antigens) immobilized on a transducer to antigens (antibodies) in the sample media can produce analytical signals dynamically varying with the concentrations of analytes of interest. Matharu et al (2009a) obtained an accurate and specific human plasma LDL immunosensor based on SPR and QCM by immobilizing anti-apolipoprotein B (AapoB) onto self-assembled monolayer of 4-aminothiophenol (AT). The AapoB/AT/Au immunosensor detected LDL up to 0.252 μM (84 mg/dl) and 0.360 μM (120 mg/dl) with sensitivity of 475.39 Hz/μM and 977.96 m°/μM by QCM and SPR techniques, respectively.…”
Section: Piezoelectric Ldl Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations